2004
DOI: 10.4161/cbt.3.5.810
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Expression and Sensitivity to Paclitaxel in Breast Cancer

Abstract: ACKNOWLEDGEMENTS Research Paper Estrogen Receptor Expression and Sensitivity to Paclitaxel in Breast Cancer ABSTRACTA retrospective analysis of CALGB trial 9344 suggested paclitaxel administration following cyclophosphamide and doxorubicin adjuvant chemotherapy is most beneficial for patients with ERα negative (ERα-) breast cancer. Since the cytotoxic effects of paclitaxel are cell cycle dependent, we postulated that the relationship between ERα and the effectiveness of adjuvant paclitaxel reflects the observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Cumulative data from clinical observations and retrospective analyses suggested that ER status might affect the therapeutic efficacy of paclitaxel because it has been observed that paclitaxel exhibited less effect in patients with ER+ breast tumors than those with ER tumors (7,9,16). Moreover, the phenomenon of ER-mediated resistance to paclitaxel has also been observed in in vitro experiments (17,41). However, most of these results were obtained based on comparative studies between the tumor cell lines derived from different individuals (17).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Cumulative data from clinical observations and retrospective analyses suggested that ER status might affect the therapeutic efficacy of paclitaxel because it has been observed that paclitaxel exhibited less effect in patients with ER+ breast tumors than those with ER tumors (7,9,16). Moreover, the phenomenon of ER-mediated resistance to paclitaxel has also been observed in in vitro experiments (17,41). However, most of these results were obtained based on comparative studies between the tumor cell lines derived from different individuals (17).…”
Section: Discussionmentioning
confidence: 53%
“…However, most of these results were obtained based on comparative studies between the tumor cell lines derived from different individuals (17). Although some paired cell lines were derived under the selective pressure of a low/no estrogen environments, these tumor cells are still not likely to be isogenic because many features, including their proliferative capacity, might have changed due to genetic alterations (41). Thus, it is difficult to elucidate the cellular and molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Vikhanskaya et al (1998) reported that the inactivation of p53 is susceptible to Paclitaxel in ovarian cancer (Rouzier et al, 2005), and Reinecke et al (2000a, b) described the expression and function of P-glycoprotein in renal cell carcinoma. Moreover, the overexpression of antiapoptotic genes (Wang et al, 2005), the upregulation of cyclin A (Takahashi et al, 2005), the overexpression of oestrogen receptor (Dougherty et al, 2004), and the reduced expression of tau (Rouzier et al, 2005) have all been reported as Paclitaxel susceptibility markers in breast cancer. As for colorectal cancers, the expression of MDR-1, bcl-2, and bax each contribute to Paclitaxel sensitivity (Sharma et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…ZR75.1 and MCF-7 cells were used for further in vitro studies. These cells are known to be relatively resistant to paclitaxel (14). T47D and MDA-MB 435 cells could not be successfully transfected with anti-tau siRNA.…”
Section: Down-regulation Of Tau Expression In Breast Cancer Cells Incmentioning
confidence: 99%